Approaches to a crisis in early pregnancy: an explorative qualitative study of medical students and doctors in training in Ireland, using a story completion model - Mary Higgins; Sharon Cooley; Deirdre Hayes-Ryan; Brendan Dempsey (Sexual and Reproductive Health Matters)
A crisis in early pregnancy can be due to an unplanned pregnancy or a suspected abnormality. Pregnant people have the right to unbiased and comprehensive advice of all options from healthcare providers. Using story completion models (SCM), the aim of this qualitative study was to explore the attitudes of medical students and doctors in training towards crisis pregnancy, specifically two scenarios: early unplanned pregnancy and fatal fetal abnormality (anencephaly). Participants were invited from medical students attending University College Dublin (UCD) and trainees in Obstetrics and Gynaecology at the Royal College of Physicians of Ireland (RCPI) from July to December 2022. SCM involves giving the consenting participant an introduction to a hypothetical situation that acts as the beginning of a story and asking them to complete it. Stories were compiled and analysed using thematic analysis. Research Ethics Committee approval was given by both UCD and the RCPI. The standards for reporting qualitative research guidelines were followed. Eight doctors in training and six medical students consented to participate in the study; all but two medical students completed both stories to the required word count, giving 25 stories for analysis. For both situations, stories described a variety of approaches, all of which were based on the person's, or couple's, wishes, from continuing in pregnancy to deciding to end the pregnancy. SCM allowed detailed analysis of potentially sensitive subjects such as pregnancy options. This study showed that participating medical students and doctors in training recognise that pregnant people have the right to all choices in crisis pregnancy.